2012
DOI: 10.1039/c2an35047e
|View full text |Cite
|
Sign up to set email alerts
|

Expression of membrane-associated proteins within single emulsion cell facsimiles

Abstract: MreB is a structural membrane-associated protein which is one of the key components of the bacterial cytoskeleton. Although it plays an important role in shape maintenance of rod-like bacteria, the understanding of its mechanism of action is still not fully understood. This study shows how segmented flow and microdroplet technology can be used as a new tool for biological in vitro investigation of this protein. In this paper, we demonstrate cell-free expression in a single emulsion system to express red fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Lipid-free experiments performed with water/oil/water (w/o/w) double emulsions (Martino et al 2012a), and water/oil (w/o) droplets (Chanasakulniyom et al 2012), showed that a freshly synthesised fusion protein, comprised of MreB joined to red fluorescent protein (RFP), accumulated at the surfactant-based emulsion interface.…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
“…Lipid-free experiments performed with water/oil/water (w/o/w) double emulsions (Martino et al 2012a), and water/oil (w/o) droplets (Chanasakulniyom et al 2012), showed that a freshly synthesised fusion protein, comprised of MreB joined to red fluorescent protein (RFP), accumulated at the surfactant-based emulsion interface.…”
Section: Downloaded By [University College London] At 07:47 24 June mentioning
confidence: 99%
“…As a result, diffusion pathways as well as protein synthesis rates in vitro can strongly differ from cellular behavior in vivo . To more closely address the complex membrane‐encompassed environment of living cells in vitro, CFPS has been confined to microscopic water‐in‐oil (W/O)‐emulsions, semi‐permeable liposomes and polymersomes, coacervates, or microclays . Beyond this, hydrogel‐based materials have attracted growing attention due to their wide range of applicable natural and synthetic polymers, which can be crosslinked by bio‐orthogonal strategies .…”
Section: Introductionmentioning
confidence: 99%
“…1932-1058/2013/7(1)/014108/12/$30.00 V C 2013 American Institute of Physics 7, 014108-1 fluorescent proteins, a reductase enzyme, and the membrane-associated protein MreB in pl droplets-in-oil. 7,8 Once biomolecules have been enclosed in a droplet compartment, additional reagents can be supplied by merging the original droplet with a second droplet that carries the desired molecules. 9 For example, in the case of cell-free protein expression, it can be advantageous to delay the introduction of the DNA plasmid until the droplet with the ribosomal extract is at a defined position in an array, or to replenish the molecules that supply metabolic energy after a certain period of protein expression.…”
Section: Introductionmentioning
confidence: 99%